2016
DOI: 10.1063/1.4960123
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic corrections from analytic non-Maxwellian distribution functions in magnetized plasmas

Abstract: In magnetized plasma physics, almost all developed analytic theories assume a Maxwellian distribution function (MDF) and in some cases small deviations are described using the perturbation theory. The deviations with respect to the Maxwellian equilibrium, called kinetic effects, are required to be taken into account specially for fusion reactor plasmas. Generally, because the perturbation theory is not consistent with observed steady-state non-Maxwellians, these kinetic effects are numerically evaluated by ver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 69 publications
2
35
0
2
Order By: Relevance
“…The second reason of this failure is the misconception of the fluid reduction from the kinetic Boltzmann description, and more generally of the fluid theory: it has been difficult to expand this fluid theory here for nonequilibria based on the properties of MDFs without falling into the usual limitations, but a summarized point of view of the state-of-the-art of the fluid reduction since the 1870's clarifies our novel approach. The introduced INMDFs represent an extension of the usual fluid theory since (i) it has been shown (Izacard 2016b) The INMDF seems to prove that all accepted misunderstandings about the fluid theory mentioned previously can be bypassed.…”
Section: )mentioning
confidence: 92%
See 1 more Smart Citation
“…The second reason of this failure is the misconception of the fluid reduction from the kinetic Boltzmann description, and more generally of the fluid theory: it has been difficult to expand this fluid theory here for nonequilibria based on the properties of MDFs without falling into the usual limitations, but a summarized point of view of the state-of-the-art of the fluid reduction since the 1870's clarifies our novel approach. The introduced INMDFs represent an extension of the usual fluid theory since (i) it has been shown (Izacard 2016b) The INMDF seems to prove that all accepted misunderstandings about the fluid theory mentioned previously can be bypassed.…”
Section: )mentioning
confidence: 92%
“…These new parameters have been physically interpreted in Ref. (Izacard 2016b) as a displacement of a population of particles in the velocity phase space due to an external source of energy. The efficiency of the INMDF to describe a localized super-thermal tail is shown in Fig.…”
Section: )mentioning
confidence: 99%
“…The plausibility of this hypothesis is supported by recent gyrokinetic simulations performed by Churchill et al 22 . Another important factor is the effect of the enhanced suprathermal population on Langmuir probe characteristics [23][24][25][26] : Ďuran et al 27 have shown that a more sophisticated interpretation of probe results can reduce but not eliminate the discrepancy. Resolution of this discrepancy is critical as excessive heat loads could erode and severely limit the lifetimes of the divertor target plates.…”
Section: Introductionmentioning
confidence: 99%
“…n c 75,(26) where n c ∈ [−154, 100] is the cell number counting from the centre of the temperature ramp. Cell size in mfp's was varied between simulations to scan a range of collisionali-…”
mentioning
confidence: 99%
“…The density and velocity distributions in nonequilibrium complex systems have been observed in astronomy and astrophysics, space plasmas, complex fluids, molecular dynamics, nuclear and atomic physics, condensed matter physics, chemical reaction systems, and biological systems. It has been found that the velocity distributions of the charged particles in the systems with long-range correlations are quite far from the Maxwellian distribution, with long energetic tails [1][2]. Recently, nonextensive statistics proposed by Tsallis has attracted great attention of scientific researchers, a new statistics which can study the complex systems beyond thermodynamic equilibrium [3][4].…”
Section: Introductionmentioning
confidence: 99%